Printing students and faculty - Dearinger::::::photographer::: (1954)
On back: "Left to right: C.H. Gregory, Herman [sp?] Rose, Delbert Bratright, Robert Hoenig, Bruce Arnold, Heidelburg Representative, Robert Kuhn (or Richard Kuhn?), Bill Clingingsmith, Guy Culbertson, A.M. Fellows"